2016
DOI: 10.1007/s00467-016-3533-z
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside-induced nephrotoxicity in children

Abstract: Aminoglycoside antibiotics, in particular gentamicin and tobramycin, are still commonly used in paediatric clinical practice. These drugs cause nephrotoxicity, which particularly affects the proximal tubule epithelial cells due to selective endocytosis and accumulation of aminoglycosides via the multi-ligand receptor megalin. Recent epidemiological studies, using more widely accepted definitions of acute kidney injury (AKI), have suggested that AKI may occur in between 20 and 33 % of children exposed to aminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
2
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 72 publications
2
68
2
10
Order By: Relevance
“…Interestingly, no significant differences in KIM‐1/creatinine ratios between study visits were found in our study, while a recent review suggests that KIM‐1 outperforms other biomarkers in preclinical and clinical studies of aminoglycoside‐induced nephrotoxicity . This can be explained by the relatively high lower limit of quantitation (LLOQ) of 0.6 μg/L of our KIM‐1 assay, while the median KIM‐1 reference value for healthy children is expected to be around 0.410 μg/L (interquartile range 0.226–0.703 μg/L) .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Interestingly, no significant differences in KIM‐1/creatinine ratios between study visits were found in our study, while a recent review suggests that KIM‐1 outperforms other biomarkers in preclinical and clinical studies of aminoglycoside‐induced nephrotoxicity . This can be explained by the relatively high lower limit of quantitation (LLOQ) of 0.6 μg/L of our KIM‐1 assay, while the median KIM‐1 reference value for healthy children is expected to be around 0.410 μg/L (interquartile range 0.226–0.703 μg/L) .…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, no significant differences in KIM-1/creatinine ratios between study visits were found in our study, while a recent review suggests that KIM-1 outperforms other biomarkers in preclinical and clinical studies of aminoglycoside-induced nephrotoxicity. 31 Those patients may be even more at risk for TIS-induced renal toxicity, since there is no recovery time in an off-period.…”
Section: Safetymentioning
confidence: 99%
“…Another advance has been in the area of AKI biomarkers. Although these biomarkers still technically detect injury after it occurs, their rise precedes that of serum creatinine concentration, leading to earlier identification of nephrotoxicity . Biomarkers have been studied most extensively in general AKI populations; however, NTx‐AKI is an especially promising area for biomarker research .…”
Section: Where We Are: Current Stage Of Ntx‐aki Risk Predictionmentioning
confidence: 99%
“…Aminoglycoside‐induced nephrotoxicity is characterized by selective targeting of the proximal tubule epithelial cells within the renal cortex. Intracellular aminoglycoside results in apoptosis and necrosis of these cells via a variety of pathways (including mitochondrial dysfunction and the release of reactive oxygen species) ( Figure ) . Aminoglycosides accumulate in proximal tubule cells through endocytosis via the multi‐ligand receptor, megalin.…”
Section: Aminoglycoside‐induced Nephrotoxicitymentioning
confidence: 99%
“…Intracellular aminoglycoside results in apoptosis and necrosis of these cells via a variety of pathways (including mitochondrial dysfunction and the release of reactive oxygen species) (Figure 1). 5 Aminoglycosides accumulate in proximal tubule cells through endocytosis via the multi-ligand receptor, megalin. Consistent with this, in megalin knockout mice, there is no renal accumulation of aminoglycosides.…”
Section: Aminoglycoside-induced Nephrotoxicitymentioning
confidence: 99%